The Press and public policy - Daly, John Charles; Sevareid, Eric; Wattenberg, Ben; Wicker, Tom; Will, George (Washington : The Institute, 1979)
This pamphlets contains important ides on current policy problems of national and international import. It further reveals why decision should be based on informed public opinion.
asm; 04/03/19
Loans
Keywords: Journalism; Government and the press